Application of Multisensory Strategies in Differentiated Classroom Learning to Overcome Reading Delay in Elementary School Students - Syerlyana, Allya; Islami, Resya Mutiara; Yanti, Frida Rizki; Kusmana, Suherli; Rahayu, Ira (JTP - Jurnal Teknologi Pendidikan, 2025)
Reading is a fundamental skill essential for elementary school students' success. However, many students experience reading delays due to learning methods that are not suited to their learning styles. These delays impact letter recognition, academic achievement, and reading comprehension. This study aims to assess the effectiveness of implementing multisensory learning strategies in Indonesian language subjects in differentiated classrooms to address reading barriers in elementary school students. Multisensory strategies engage various senses such as sight, hearing, kinesthetics, and touch, through activities such as reading with pictures, writing using textured media, and listening to audio. Differentiated learning is carried out by grouping students based on reading ability and learning style. This study used a quantitative method with a quasi-experimental one-group pretest-posttest design without a control group. The subjects were 84 third-grade students from three elementary schools in Cirebon, with a focus on 16 students with reading delays. Data were analyzed using a paired t-test. The results showed significant improvements in students' reading skills after the intervention, including letter recognition, spelling, and sentence comprehension. The novelty of this study lies in the integration of multisensory strategies with a differentiated classroom approach, a practice rarely studied in Indonesian elementary education. This research contributes to the development of adaptive and inclusive learning approaches, particularly in the development of learning strategies that are responsive to the needs of students with reading delays.